DIGGING THE ROOTS OF LOCAL HERBALIST IN BUKIDNON - Pilar Villahermosa Domagsang; Theresa Linda N. Painagan (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2023)
In the Philippines, common stories of the curative effects of the herbs were tested by traditional healers on their patients on a trial and error basis. In the province of Bukidnon, few studies relate to the unevaluated practice of herbal medicine. Nonetheless, stories of “Binisaya” or “Mananambal” – the local term for herbalists are most dwellers seek and depend on their health and relief from illnesses. This study embarked on qualitative inquiry to understand the lived experiences and uncover stories that trace the tradition and practices of the key players and partners in our communities in promoting health. The research employed a qualitative phenomenological design. Data management utilized NVivo 7 and the analysis of findings was drawn following Colaizzi’s descriptive-interpretive principles. Purposive sampling led to the conduct of key informant interviews to nine (9) respondents within Bukidnon. There are seven major themes that surfaced in the stories of local herbalists: (1) Existence is driven by Extraordinary mission; (2) Essential roles and regard in the community; (3) Extreme experiences of healing; (4) Extensive use of herbal resources with explicit measures and timing; (5) Exclusivity of prayer, ritual and sacrifices; (6) Evidence of living in simplicity; and (7) Service that is worth Emulating. The findings help us better understand the cultural, personal, and traditional considerations in the usage of herbal medicines giving emphasis on how these practices on healing methods brought wellness to the people. Keywords: Herbalist, Mananambal, Traditional Medicine, Phenomenology